Clinical Effect of Preservation or Nonpreservation of Left Colic Artery in Total Mesorectal Excision under Laparoscopy: A Meta-analysis - Jiefeng Liu; Yujing Gong; Miao He; Xinyu Zeng; Yiping Liu (Gastroenterology Research and Practice)
Background and Aims. To investigate the clinical effect of preservation or nonpreservation of the left colic artery (LCA) in total mesorectal excision (TME) under laparoscopy. Methods. The words, like “rectal cancer,” “left colonic artery,” and “laparoscopy,” were used as the retrieval terms, and the keyword retrieval method was adopted. The retrieval period was set as from January 1, 2013, to June 1, 2018. We searched databases including PubMed, Web of Science, and China National Knowledge Infrastructure (CNKI) to collect randomized and controlled trials which compared the effect of preservation or nonpreservation of the LCA in TME under laparoscopy. Two researchers independently carried out literature screening, data extraction, and literature quality evaluation; Review Manager 5.3 was used for the meta-analysis. Results. Seven studies including 1467 cases were identified for the meta-analysis. As showed by the meta-analysis, compared with the LCA nonpreservation group, the LCA preservation group had significantly reduced incidence of anastomotic leakage (OR=0.44, CI=0.30,0.65, P<0.0001) and postoperative urinary and sexual dysfunction (OR=0.26, CI=0.09,0.78, P=0.02) and significantly shorter time for intestinal function recovery (WMD=−0.26, CI=−0.41,−0.11, P=0.0008). There were no significant differences between the two groups in the duration of surgery, blood loss, number of dissected lymph nodes, or postoperative hospital stay. Conclusions. From the results, the LCA preservation group seems to achieve comparable success with acceptable safety outcomes. Therefore, this surgical method can be recommended in the clinical practice.